Bird Ringing Station Manual - Busse, Przemyslaw (De Gruyter, 2015)
In an attempt to standardize elements of the station routine, the book describes the procedures used in passerine and wader ringing stations. It offers a comparative analysis of versatile evaluation techniques such as measurements, orientation experiments and monitoring. The authors meticulously analyze different methods used to track birds, including catching passerines with mist-nets in land and wetland habitat, as well as the use of the Heligoland trap. The monograph, as a successful bid to establish a bird station routine that is favourable to both birds and ringers, will benefit all professional and amateur ringers.